Comparative effectiveness of the FINDRISC and ADA scores to predict diabetes mellitus in the presence of predisposing factors (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2023)
Background: Type 2 diabetes mellitus (DM2) is a chronic endocrine-metabolic disorder (Gagliardinoa, et al., 2016), characterized by hyperglycemia secondary to the combination of decreased insulin secretion and increased tissue resistance to the action of the same.General Objective: To establish the efficacy of the FINDRISC and ADA scores to predict diabetes mellitus in patients with predisposing factors.Methodology: The study is quantitative approach, non-experimental design, cross-sectional, observational and analytical method.Results: The FINDRISC score classified 70.3% of the participants as having a high risk of diabetes mellitus, the variables with the greatest significance were age, first-degree family history, BMI, AC, arterial hypertension and glucose > 100mg/dl. The ADA test applied to the same individuals classified 64.2% as high risk, all of its variables with statistical significance except for the antecedent of gestational diabetes; good correlation with laboratory tests.Conclusion: Easy-to-apply ADA test, in addition to predicting risk of diabetes mellitus 2, also allows establishing the diagnosis unlike the FINDRISC.
Keywords: score; FINDRISC; ADA; diabetes mellitus; prediabetes